2015
DOI: 10.1556/038.50.2015.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Plant Parasitic Nematodes Associated with Olive in Algeria

Abstract: in olive growing areas of south and north of Algeria to identify plant parasitic nematodes associated with this crop. Sixteen genera of plant-parasitic nematodes were identified. Among them four are considered as having economic importance for olive. Among these the endoparasites Pratylenchus spp. were detected in the majority of the sampled areas and were the most frequent. Meloidogyne spp. were also present in some areas. Helicotylenchus spp. were present with a high frequency in almost all surveyed sites. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Further studies conducted on vegetable crops, vineyards, olives and in natural area reported the occurrence of: Helicotylenchus pseudorobustus and Hemicycliophora (Ouanouki and Ighili, 1988), Aglenchus, Amplimerlinus, Anguina, Aphelenchus, Aphelenchoides, Boleodorus, Criconema, Criconemoides , Hemicriconemoides , Coslenchus , Gracilacus, Globodera, Ditylenchus , Hoplolaimus , Helicotylenchus, Longidorus, Meloidogyne, Nothotylenchus, Paratrichodorus , Paratylenchus , Paratylenchoides , Pratylenchus, Psilencus, Rotylenchulus, Scutellonema, Tylenchorhynchus, Rotylenchus, Rotylenchulus, Tylenchus, Tylenchulus, Trichodorus, Telotylenchus, Trophorus and Xiphinema (Bounaceur et al, 2011;Nebih-Hadj-Sadok, 2013;Hoceini et al, 2014;Chafaa et al, 2014;Berrabah et al, 2014;Hoceini, 2015;Belahmar et al, 2015;Bissaad and Bounaceur, 2016;Berrabah, 2017;Hoceini et al, 2017) and Bursaphelenchus which was detected for the first time in Algeria by Berrabah (2017).…”
Section: Main Plant Parasitic Nematodes Reported In Algeriamentioning
confidence: 99%
“…Further studies conducted on vegetable crops, vineyards, olives and in natural area reported the occurrence of: Helicotylenchus pseudorobustus and Hemicycliophora (Ouanouki and Ighili, 1988), Aglenchus, Amplimerlinus, Anguina, Aphelenchus, Aphelenchoides, Boleodorus, Criconema, Criconemoides , Hemicriconemoides , Coslenchus , Gracilacus, Globodera, Ditylenchus , Hoplolaimus , Helicotylenchus, Longidorus, Meloidogyne, Nothotylenchus, Paratrichodorus , Paratylenchus , Paratylenchoides , Pratylenchus, Psilencus, Rotylenchulus, Scutellonema, Tylenchorhynchus, Rotylenchus, Rotylenchulus, Tylenchus, Tylenchulus, Trichodorus, Telotylenchus, Trophorus and Xiphinema (Bounaceur et al, 2011;Nebih-Hadj-Sadok, 2013;Hoceini et al, 2014;Chafaa et al, 2014;Berrabah et al, 2014;Hoceini, 2015;Belahmar et al, 2015;Bissaad and Bounaceur, 2016;Berrabah, 2017;Hoceini et al, 2017) and Bursaphelenchus which was detected for the first time in Algeria by Berrabah (2017).…”
Section: Main Plant Parasitic Nematodes Reported In Algeriamentioning
confidence: 99%